HUBUNGAN KEPUASAN PASIEN ANTENATAL CARE DENGAN MOTIVASI UNTUK BERSALIN DI RUMAH SAKIT BAPTIS KEDIRI - Yusiana, Maria Anita; Sushantri, Enggar (Jurnal Penelitian STIKES Kediri, 2011)
ABSTRACT   Patients’ satisfaction is the objective of health service improvement. Satisfaction will drive them to loyally obey every treatment given and vice versa. The purpose of the research was to find out the correlation between satisfaction of antenatal care’s patients and delivery’s motivation on Kediri Baptist hospital The research was designed by correlation. The population was all of antenatal care’s patients on Kediri Baptist Hospital. The number of sample was 60 respondents and taken using Random Sampling. The independent variable was satisfaction of antenatal care’s patients while the dependent variable was delivery’s motivation. The data were analyzed using Spearman Rho with significant level α≤0.05. The result showed 50 respondents (83.3%) felt very satisfied and having high motivation (93.3%) to deliver on Kediri Baptist hospital. The result of statistical testing showed p=0.022. Therefore, Ho was rejected and Ha was accepted meaning that there was correlation between satisfaction of antenatal care’s patients and delivery’s motivation on Kediri Baptist hospital In conclusion, there was correlation between satisfaction of antenatal care’s patients and delivery’s motivation on Kediri Baptist hospital   Keywords: satisfaction, motivationn, antenatal care’s patients